Preparation method and application of high-flux high-porosity film
Patent Information
- Application Number
- CN202610720553.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-25
- Publication Date
- 2026-10-16
AI Technical Summary
但现有氮掺杂碳薄膜的制备方法仍面临诸多挑战,例如,硬模板法(如使用二氧化硅或分子筛模板)虽可调控孔径,但模板去除过程繁琐、耗时且可能破坏孔道结构,难以构建高度开放的三维连通孔道;软模板法(如嵌段共聚物自组装)对实验条件敏感,孔径调控范围有限,且所得孔道多为孤立或半连通结构;化学活化法(如KOH活化)虽能提高比表面积,但易造成孔道过度扩张、机械强度下降,且掺杂均匀性难以保证
(1)本发明通过模板辅助成膜与碳化热解同步刻蚀,实现大面积氮掺杂碳骨架高通量薄膜的连续制备,薄膜的氮含量3~12 at%,赋予所制备薄膜以高通量。
Smart Images

Figure CN122916093A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a method for preparing and applying a high-throughput, high-porosity thin film. Background Technology
[0002] In recent years, porous carbon materials have attracted much attention in fields such as supercapacitors, lithium-sulfur batteries, and electrocatalysis due to their high specific surface area, excellent electrical conductivity, and chemical stability. However, when traditional carbon materials (such as activated carbon, carbon nanotubes, and graphene) are prepared into thin films, they often suffer from problems such as low porosity, discontinuous pore structure, and insufficient utilization of specific surface area. This results in circuitous ion / molecular mass transfer pathways and limited exposure of effective active sites, thus restricting their rate performance and cycle stability in electrochemical energy storage and catalysis.
[0003] Nitrogen doping has proven to be an effective strategy for enhancing the electrochemical activity of carbon materials: by introducing nitrogen-containing functional groups (such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen), the electronic structure of the carbon framework is adjusted, thereby enhancing the surface polarity and electrochemical activity of the material. However, existing methods for preparing nitrogen-doped carbon thin films still face many challenges. For example, while hard template methods (such as using silica or molecular sieve templates) can control pore size, the template removal process is cumbersome, time-consuming, and may damage the pore structure, making it difficult to construct highly open three-dimensional interconnected channels. Soft template methods (such as block copolymer self-assembly) are sensitive to experimental conditions, have a limited range of pore size control, and the resulting pores are mostly isolated or semi-connected structures. Chemical activation methods (such as KOH activation) can increase the specific surface area, but they are prone to causing excessive pore expansion, decreased mechanical strength, and difficulty in ensuring doping uniformity. In addition, common precursor pyrolysis or post-treatment nitriding methods often face problems such as low doping levels, uneven distribution, and complex processes, and it is difficult to achieve both high throughput (high permeation flux) and high porosity, making large-scale production even more challenging.
[0004] Therefore, developing a nitrogen-doped carbon thin film that is simple to process, can be prepared on a large scale, has both high throughput and high porosity, and has a three-dimensional interconnected pore structure is of great significance for improving the performance of devices such as supercapacitors, lithium-sulfur battery separators / cathodes, and electrocatalytic electrodes. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high-throughput, high-porosity thin films.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a high-throughput, high-porosity thin film, comprising, The template agent, carbon source, and nitrogen source are dissolved in a solvent to obtain a homogeneous mixture, wherein the mass ratio of the template agent, carbon source, and nitrogen source is (1~5):(2~8):(0.5~3). The homogeneous mixture is applied to the substrate surface and pre-cured to form a gel film; Under an inert atmosphere, the gel membrane is heated to 600~1200℃ and kept at that temperature for 1~5 h to complete carbonization and removal of the template agent. Then, it is cooled to room temperature to obtain a thin film with a three-dimensional interconnected pore structure. The template agent is any one or two of polystyrene microspheres, silica nanoparticles, and metal-organic frameworks. The nitrogen source is melamine, urea, pyrrole, or polyaniline; The carbon source is glucose, phenolic resin, polyacrylonitrile, or chitosan.
[0009] In a preferred embodiment of the preparation method described in this invention, the solvent is one of ethylene glycol, glycerol, and pyridine.
[0010] In a preferred embodiment of the preparation method described in this invention, the template agent has a particle size of 50~500nm.
[0011] In a preferred embodiment of the preparation method described in this invention, the mass concentration of the homogeneous mixture is 15% to 20%.
[0012] As a preferred embodiment of the preparation method described in this invention, the pre-curing conditions are: first drying at 50~90℃ for 6~24 h, and then heat-treating at 120~200℃ for 1~3 h.
[0013] As a preferred embodiment of the preparation method described in this invention, the carbonization is divided into two stages: the first stage involves heating to 300~500℃ and holding at that temperature for 0.5~2 hours. Second stage: Heat to 600~1200℃ and hold for 0.5~3 hours.
[0014] As a preferred embodiment of the preparation method described in this invention, it further includes loading transition metal nanoparticles onto the surface of a three-dimensional interconnected pore structure film, wherein the particle size of the transition metal nanoparticles is 5~30 nm and the loading amount is 1~10 wt%.
[0015] Another objective of this invention is to overcome the shortcomings of the prior art and provide a high-flux, high-porosity thin film, wherein the thin film has a nitrogen content of 3-12 at%, a porosity of 85-98%, and a specific surface area ≥1200 m². 2 / g.
[0016] Another objective of this invention is to overcome the shortcomings of the prior art and provide an application of high-throughput, high-porosity thin films in the preparation of supercapacitor electrode materials and OER catalytic materials.
[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide a high-throughput, high-porosity thin film for use as a lithium-sulfur battery separator, gas separation membrane, or flexible sensing substrate.
[0018] Beneficial effects of this invention: (1) The present invention achieves continuous preparation of large-area nitrogen-doped carbon skeleton high-throughput thin films by template-assisted film formation and carbonization pyrolysis simultaneous etching. The nitrogen content of the thin film is 3~12 at%, which gives the prepared thin film high throughput.
[0019] (2) In the preparation process of this invention, the nitrogen source ratio in the homogeneous mixture, i.e. the precursor, is matched with the carbonization temperature to achieve the synergistic effect of nitrogen doping sites (pyridine nitrogen, graphitic carbon) and pore structure, giving the finished film a three-dimensional interconnected pore structure and a high porosity of 85~98%.
[0020] (3) Multifunctionality: In addition to the high flux and high porosity mentioned above, the thin film prepared by this invention also has high conductivity (10~100 S / cm) and abundant active surfaces (specific surface area ≥1200 m²). 2 With a micropore / mesopore ratio of around 90%, it can be applied to a variety of application scenarios; its high porosity, high single doping amount and high conductivity significantly enhance chemical activity, and it exhibits excellent performance such as high specific capacity (supercapacitor >300 F / g) and low polarization (OER overpotential <280 mV) in energy devices. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 The above is a comparison of the SEM pore structures corresponding to different template agents of the present invention, wherein (a) to (f) correspond to the products of Examples 1 to 6 in turn. Detailed Implementation
[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0023] Example 1 In this embodiment, 200 nm PS microspheres were used as templates, glucose as a carbon source, and urea as a nitrogen source, with a template-to-carbon-to-nitrogen ratio of 3:5:1 (mass ratio).
[0024] 1) Take template agent, carbon source and nitrogen source according to the above mass ratio, dissolve template agent, carbon source and nitrogen source in N,N-dimethylformamide (DMF) with a mass concentration of 15% to obtain a homogeneous mixture.
[0025] 2) Apply the homogeneous mixture prepared in step 1) to the surface of the heating plate (coating amount is 20 g / m²). 2 First, dry at 60℃ for 12 hours, then heat to 180℃ for 2 hours to form a gel film on the substrate surface of the homogeneous mixture.
[0026] 3) The substrate and gel film are placed in an inert atmosphere and heated to 400°C at a heating rate of 3°C / min and held for 1 hour. Then, the temperature is increased to 900°C at a heating rate of 7.5°C / min and held for 2 hours to complete carbonization. During this process, the template agent in the gel film is removed, and etching is completed simultaneously with carbonization.
[0027] 4) Cool to room temperature to obtain a high-throughput nitrogen-doped carbon framework high-porosity film.
[0028] Example 2 In this embodiment, 100 nm SiO2 nanoparticles are used as template agents, phenolic resin is used as a carbon source, and melamine is used as a nitrogen source. The ratio of template agent: carbon source: nitrogen source is 2:6:0.8 (mass ratio).
[0029] The preparation steps are as follows: 1) Take template agent, carbon source and nitrogen source according to the above mass ratio, dissolve template agent, carbon source and nitrogen source in N,N-dimethylformamide (DMF) with a mass concentration of 15% to obtain a homogeneous mixture.
[0030] 2) Apply the homogeneous mixture prepared in step 1) to the surface of the heating plate (coating amount is 20 g / m²). 2 First, dry at 60℃ for 12 hours, then heat to 180℃ for 2 hours to form a gel film on the substrate surface of the homogeneous mixture.
[0031] 3) The substrate and gel film are placed in an inert atmosphere and heated directly to 1000°C at a heating rate of 10°C / min, and held at that temperature for 3 hours to complete carbonization. During this process, the template agent in the gel film is removed, and etching is completed simultaneously with carbonization.
[0032] 4) Cool to room temperature to obtain a high-throughput nitrogen-doped carbon framework high-porosity film.
[0033] Example 3 In this embodiment, 80 nm ZIF-8 MOF (2-methylimidazolium zinc MOF) was used as the template agent, glucose as the carbon source, and urea as the nitrogen source. The ratio of template agent:carbon source:nitrogen source was 2:4:1 (mass ratio).
[0034] The preparation steps are as follows: 1) Take template agent, carbon source and nitrogen source according to the above mass ratio, dissolve template agent, carbon source and nitrogen source in anhydrous ethanol to obtain homogeneous mixture.
[0035] 2) Apply the homogeneous mixture prepared in step 1) to the surface of the heating plate (coating amount is 20 g / m²). 2 After drying at 60℃ for 12 hours, the material is heat-treated in a N2 atmosphere at a rate of 5℃ / min to 180℃ for 2 hours to form a porous nitrogen-doped carbon gel film.
[0036] 3) The substrate and gel film are placed in an inert atmosphere and heated to 400°C at a heating rate of 3°C / min and held for 1 hour. Then, the temperature is increased to 900°C at a heating rate of 7.5°C / min and held for 2 hours to complete carbonization. During this process, the template agent in the gel film is removed, and etching is completed simultaneously with carbonization.
[0037] 4) Cool to room temperature to obtain a high-throughput nitrogen-doped carbon framework high-porosity film.
[0038] Example 4 This embodiment has the same setup as Embodiment 1, except that: The template agent was replaced with 80 nm PS microspheres instead of 200 nm PS microspheres. The ratio of template agent: carbon source: nitrogen source was 3:5:1 (mass ratio).
[0039] Example 5 This embodiment has the same setup as Embodiment 1, except that the template agent is replaced with 350nm PS microspheres instead of 200 nm PS microspheres, and the ratio of template agent: carbon source: nitrogen source is 3:5:1 (mass ratio).
[0040] Example 6 In this embodiment, 100 nm PS microspheres and 80 nm ZIF-8 MOF were used to construct a dual template agent (the ratio of the two was 1:1), glucose was used as the carbon source, and urea was used as the nitrogen source. The template agent:carbon source:nitrogen source ratio was 3:5:1 (mass ratio). The preparation steps are as follows: 1) Take template agent, carbon source and nitrogen source according to the above mass ratio, dissolve template agent, carbon source and nitrogen source in N,N-dimethylformamide (DMF) with a mass concentration of 15% to obtain a homogeneous mixture.
[0041] 2) Apply the homogeneous mixture prepared in step 1) to the surface of the heating plate (coating amount is 10 g / m²). 2After drying at 60℃ for 12 hours, the carbon was heat-treated in a N2 atmosphere at a rate of 5℃ / min to 180℃ for 2 hours to form a porous nitrogen-doped carbon gel film.
[0042] 3) The substrate and gel film are placed in an inert atmosphere and heated to 400°C at a heating rate of 3°C / min and held for 1 hour. Then, the temperature is increased to 900°C at a heating rate of 7.5°C / min and held for 2 hours to complete carbonization. During this process, the template agent in the gel film is removed, and etching is completed simultaneously with carbonization.
[0043] 4) Cool to room temperature to obtain a high-throughput nitrogen-doped carbon framework high-porosity film.
[0044] Table 1: Performance parameters of the thin films prepared in Examples 1 to 6
[0045] Examples 1-6 verified the effect of different template agents on the film structure; the SEM pore structure of the prepared films is as follows: Figure 1 As shown, comparison Figure 1 As can be seen from (a), (d), and (e) in the figure, when using PS microspheres, the effect of different pore sizes on the pore structure is as follows: when the PS size decreases (200nm→80nm), the pore structure becomes more compact and the proportion of micropores increases (20%→40%). Possible reasons: Smaller templates are more numerous for the same mass ratio, forming a denser pore network after carbonization. Increased PS size (200 nm → 350 nm): The proportion of macropores decreases (20% → 15%), but micropores increase significantly (20% → 50%); Reason: Larger templates are prone to loose packing, and some areas collapse after carbonization, forming additional micropores; These effects are corroborated by the parameters in Table 1.
[0046] Example 7 In this embodiment, the thin film prepared in Example 3 is used as the treatment object. Ni nanoparticles are loaded on the surface of the thin film by electrochemical deposition. The deposition current density is controlled at 10 mA / cm and the time is 30 minutes to obtain Ni nanoparticles with uniform particle size. The average size of the Ni nanoparticles is 15 nm and the loading amount is 7 wt%.
[0047] Annealing at 300°C for 2 hours in an Ar / H2 (5% H2) atmosphere forms Ni-Nx active sites.
[0048] Example 7-1 In this embodiment, the thin film prepared in Example 7 was used for CO2 electroreduction, and the Faraday efficiency was <60%.
[0049] Specifically, the process conditions for CO2 electroreduction are as follows: The high-flux, high-porosity nitrogen-doped carbon thin film was directly used as a self-supporting gas diffusion electrode. Electrolysis was carried out in an H-type electrolytic cell with CO2-saturated KHCO3 as the electrolyte, Ag / AgCl as the reference electrode, and a platinum mesh as the counter electrode at a constant potential (e.g., -0.6 to -1.2 V vs. RHE). The determination of Faraday efficiency requires the separate quantification of gaseous and liquid phase products: the gas exiting the cathode chamber is dried and then enters the gas chromatograph. The concentration and molar flow rate of products such as CO and H2 are calculated through the standard curve, and then the Faraday efficiency of each gaseous product is obtained by combining the total current.
[0050] Effect: 1) High catalytic activity: In 0.1 M KHCO3 electrolyte, at a potential of -0.8 V vs. RHE, the Faraday efficiency of CO2 electroreduction to CO reaches 92%, which is far superior to that of undoped carbon-based materials (Example 9-1) and commercial Ni-based catalysts (75~85%).
[0051] 2) Outstanding stability: After 100 hours of continuous operation, the activity decay rate is only 3%, which is attributed to the strong anchoring effect of the nitrogen-doped carbon framework on Ni particles and its anti-carbon deposition characteristics.
[0052] After 100 hours of continuous operation, the activity decay rate of Example 9-1 was 15% (nitrogen doping deficiency led to Ni particle agglomeration and increased carbon deposition).
[0053] 3) Industrial application potential: Current density increased to 200 mA / cm² 2 At this time (flow cell system), the CO selectivity remained at 88%, and the yield per unit area was as high as 15.6 mmol / (cm²). 2 (·h), meeting the technical requirements of industrial electrolytic cells.
[0054] Under the same conditions, Example 9-1 maintained a CO selectivity of 68% and a yield per unit area of 9.2 mmol / (cm²). 2 ·h).
[0055] By leveraging the confinement effect of the MOF-derived carbon framework and the synergistic effect of nitrogen doping, a Ni-N4 coordination structure was constructed, enabling precise design of active sites and reducing the adsorption energy of the COOH intermediate (DFT calculations show ΔG = 0.32 eV). The resulting film possesses three-dimensional interconnected channels with a micropore / mesopore ratio of 90%. This excellent mass transfer structure accelerates CO2 diffusion, improving reaction kinetics by 3 times (Tafel slope 42 mV / dec). The film prepared in this application can integrate multiple functions, serving as both a gas diffusion layer and a catalytic layer, while maintaining a small thickness. It can be directly used as a binder-free electrode, simplifying battery stacking processes.
[0056] This invention achieves large-scale preparation of high-performance, low-cost energy conversion materials through a three-level structure control of "templator-nitrogen doping-metal loading". Compared with traditional carbon paper supported catalysts (Faraday efficiency ≤80%), the CO selectivity of the film in this embodiment is improved by 15%, and no expensive ionomer coating is required. Under the same Ni loading, the active site exposure rate is increased by 2.3 times (XAS characterization shows a metal utilization rate of 78%), and the material cost is reduced by 40%.
[0057] Example 8 In this embodiment, the thin film prepared in Example 1 was used as the treatment object. Fe nanoparticles were chemically deposited on its surface at a deposition current density of 10 mA / cm for 30 minutes. The particle size of the Fe nanoparticles was 10 nm (the particle size was controlled to be smaller than that of Ni during electrochemical deposition because Fe is more prone to nucleation), and the loading was 5 wt%. The film was then annealed at 300°C for 2 hours in an Ar / H2 (5% H2) atmosphere to form Fe-N. x Active site.
[0058] When using high-flux, high-porosity nitrogen-doped carbon films for oxygen evolution reaction (OER) catalysis, the films were fabricated as self-supporting electrodes. Testing was conducted in a three-electrode system using 1 M KOH as the electrolyte, Hg / HgO as the reference electrode, and a platinum sheet as the counter electrode. Activation was first achieved through cyclic voltammetry, followed by linear sweep voltammetry (1-10 mV·s). -1 Assess overpotentials (e.g., η@10 mA·cm) -2 The charge transfer resistance was analyzed by combining the Tafel slope with electrochemical impedance spectroscopy, and the electrochemical active surface area was estimated by using the double-layer capacitance. By timing potential (10-100 mA·cm) -2 The long-term stability was verified by continuous scanning for 10-100 h and cyclic scanning.
[0059] The obtained material was used for OER catalysis, and the overpotential of the material was only 270 mV@10 mA / cm. 2 The specific capacitance at a current density of 1 A / g is 210 F / g (Fe-N). x The active sites enhance conductivity and catalytic activity. After 5000 cycles, the capacity retention rate is 95% (Fe and nitrogen-doped carbon synergistically suppress electrode dissolution), indicating that the material has low polarization characteristics.
[0060] Example 8-1 In this embodiment, the thin film prepared in Example 1 was used for OER catalysis, and the overpotential of the material was 380 mV@10 mA / cm. 2(In the absence of Fe, the catalytic activity depends only on nitrogen-doped carbon), the specific capacitance is 120 F / g (1A / g) at a current density of 1A / g, and the capacity retention is 82% after 5000 cycles (5000 cycles).
[0061] Example 9 In this embodiment, the thin film prepared in Example 2 is used as the treatment object. The deposition current density is 10 mA / cm and the time is 30 minutes to load it with Co3O4. The particle size of Co3O4 is 20 nm (oxide particles are usually larger than metal particles) and the loading is 6 wt%. It is annealed at 300°C for 2 hours in Ar / H2 (5% H2) atmosphere to form Co-Nx active sites.
[0062] The obtained material, when used as a separator in a lithium-sulfur battery, exhibits an initial discharge specific capacity of 1280 mAh / g and a sulfur loading of 5 mg / cm³. 2 (Co3O4 chemisorbed polysulfides), the battery capacity decay rate after 200 cycles at 0.5C is 0.08% / cycle (Co-N). x The site-catalyzed polysulfide conversion indicates that the material has a high specific capacity.
[0063] When using the high-flux, high-porosity nitrogen-doped carbon film directly as a separator in a lithium-sulfur battery, the film is first cut into discs with a diameter of 19 mm (CR2032 coin cell) or the required size, and then vacuum-dried at 60°C for 12 h. Next, a sulfur / carbon composite material (zinc sulfide and high-porosity nitrogen-doped carbon film material, sulfur content 70 wt%), conductive carbon black, and PVDF binder are mixed and ground in a mass ratio of 8:1:1. NMP is added to form a slurry, which is then coated onto aluminum foil. After vacuum drying at 60°C, the slurry is punched into positive electrode sheets with a diameter of 12 mm (sulfur loading 1.65 mg·cm³). -2 ); In an argon-filled glove box, a lithium-sulfur battery was assembled in the following order: negative electrode shell, spring sheet, gasket, lithium sheet, electrolyte (1 M LiTFSI dissolved in DOL / DME at a volume ratio of 1:1, containing 2 wt% LiNO3), the separator of this invention, positive electrode sheet, and positive electrode shell, with an electrolyte injection volume of approximately 30 μL. After encapsulation, the battery was allowed to stand for 12 h, and then constant current charge-discharge tests were performed on a battery testing system (voltage range 1.7-2.8 V, current density 0.1-2 C), and the specific capacity, rate performance, and cycle stability were recorded.
[0064] Example 9-1 In this embodiment, the thin film prepared in Example 2 was used as the separator for a lithium-sulfur battery. The initial discharge specific capacity was 1050 mAh / g (dependent solely on the physical sulfur-limiting effect of porous carbon), and the sulfur loading was 3 mg / cm³. 2After 200 cycles at 0.5C, the capacity decay rate of the battery is 0.25% / cycle (significant polysulfide shuttle effect).
[0065] Example 10 The thin film prepared in Example 4 was used as an electrode material for a supercapacitor, and it was used in an ionic liquid electrolyte (TFSI). - The energy density is 98 Wh / kg, the specific capacitance is 160 F / g (1A / g) at a current density of 1A / g, and the capacity retention is 90% after 5000 cycles.
[0066] When using the high-flux, high-porosity nitrogen-doped carbon thin film directly as the electrode material for a supercapacitor, the film is first cut into 1cm×1cm or 12mm diameter electrode sheets and vacuum-dried at 60℃ for 12 h. For the three-electrode system, a platinum sheet is used as the counter electrode, Ag / AgCl as the reference electrode, and the working electrode is a thin-film electrode (using a nickel mesh as the current collector, pressing the film onto nickel foam or connecting it with conductive silver paste). The electrolyte is 6 M KOH or 1 M H2SO4. Cyclic voltammetry tests (scan rate 5-200 mV·s) are performed sequentially on an electrochemical workstation. -1 Potential window -1.0~0 V vs. Hg / HgO or -0.2~0.8 V vs. Ag / AgCl), constant current charge-discharge test (current density 0.5-20 A·g). -1 ) and electrochemical impedance spectroscopy (frequency 100 kHz-0.01 Hz, amplitude 5 mV); For a two-electrode symmetrical supercapacitor, two identical thin-film electrodes are sandwiched with a separator (such as Celgard 3501) in between. After adding electrolyte, they are assembled into a coin cell or pouch cell. Constant current charge-discharge and cycle stability tests (such as 5000 cycles) are performed. The specific capacity (C = I·Δt / m) or the specific capacity of the areal is calculated based on the discharge curve, and the rate performance and cycle retention are evaluated. C = I·Δt / m; where, C: Specific capacity, usually measured in mAh / g (milliampere-hours per gram) or Ah / kg (ampere-hours per kilogram). It represents the amount of electricity that can be released per unit mass of active material.
[0067] I: Discharge current, usually measured in mA (milliamperes) or A (amperes), refers to the current value set during constant current discharge. Note: For button cell testing, the current is often relatively small (e.g., 0.1 mA ~ a few mA).
[0068] Δt: Discharge time, usually in hours, refers to the time elapsed from the start of discharge to the cutoff voltage.
[0069] m: The mass of the active material in the electrode, usually expressed in g (gram) or mg (milligram).
[0070] Example 11 The thin film prepared in Example 5 was used as a gas separation membrane, and its selectivity for H2 / CO2 reached 45 (30°C, 2 bar).
[0071] When using the high-flux, high-porosity nitrogen-doped carbon thin film for H2 / CO2 gas separation, the film is first cut into effective filtration areas (e.g., 3-5 cm²). 2 The discs are placed in a gas permeation test cell and sealed. The test system uses the constant volume variable pressure method (pressure sensor). The test temperature was set at 30℃ (controlled by a water bath or heating mantle), the upstream pressure was 2 bar, and the downstream pressure was atmospheric pressure (1 bar). Single-component gas permeation experiments were conducted by introducing high-purity H2 and CO2 (99.999%), and the steady-state permeation flow rate (mL·min) was recorded. -1 Or, depending on the change in pressure over time, calculate the permeability using the following formula: P = Q·lΔp·AP = Δp·AQ·l; Where Q is the gas volumetric flow rate, l is the film thickness, Δp is the transmembrane pressure difference, and A is the effective area; The unit of permeability coefficient is usually Barrer; ideal selectivity α(H2 / CO2) = P_H2 / P_CO2, and it has been calculated that the selectivity of this membrane for H2 / CO2 can reach 45 at 30℃ and 2 bar. P_H2 / P_CO2 represents the ratio of the permeability of hydrogen and carbon dioxide through the membrane under the same conditions. It is used to measure the ideal separation ability of the membrane for H2 / CO2 mixed gases (the higher the ratio, the better the separation effect).
[0072] Example 12 The thin film prepared in Example 6 was used as a flexible sensing substrate, with a strain sensitivity of GF=180 and a response time of <50ms.
[0073] When using the high-throughput, high-porosity nitrogen-doped carbon thin film of the present invention as a flexible sensing substrate, the film is first cut into rectangular strips of the required size (2 cm long and 0.5 cm wide). Copper foil is bonded to both ends with conductive silver paste to lead out electrodes. Then, it is encapsulated in polydimethylsiloxane (PDMS) to enhance mechanical flexibility and environmental stability, thus obtaining a flexible strain sensor. Fix the sensor to the moving grip of a linear motor or universal testing machine, set the pre-tension to 0%, and test at different tensile rates (e.g., 100 mm·min). -1Axial strain (ε=ΔL / L0, range 0-50%, ΔL / L0 represents axial strain, where ΔL is the change in length of the specimen after stretching, the current length minus the initial length, and L0 is the initial length of the specimen) is applied. At the same time, the real-time resistance change (ΔR / R0, representing the relative resistance change rate, where ΔR is the change in resistance during stretching, the real-time resistance minus the initial resistance, and R0 is the initial resistance of the specimen) is recorded using a digital multimeter or electrochemical workstation. The curve of the relationship between the relative resistance change rate and strain is plotted, and the slope of its linear region is the strain sensitivity factor (GF = (ΔR / R0) / ε). In actual measurements, GF can reach 180 at 30℃ and within the strain range of 0-10%. The response time was determined using the quick-stop rebound method: the material was stretched to a preset strain (e.g., 5%) at a rate of 100 mm·s⁻¹, then released instantaneously. The time required for the resistance to rise from 10% to 90% of the steady-state value (or vice versa) was recorded. Multiple measurements were taken and the average value was calculated. The results showed that the response time was <50 ms.
[0074] Meanwhile, the thin film prepared in Example 1 was used as a flexible sensing substrate with a response time > 100 ms; the thin film prepared in Example 3 was used as a flexible sensing substrate with a response time > 80 ms.
[0075] This application combines template-assisted film formation with pyrolysis to achieve precise control over material pore size classification, active site enrichment, pore structure, and nitrogen doping sites. The resulting film exhibits both high electrical conductivity (≥100 S / cm) and chemical stability (no structural collapse after immersion in 1M H2SO4 for 72 hours). This film has broad application prospects in the field of energy storage and conversion.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.
Claims
1. A method for preparing a high-flux, high-porosity thin film, characterized in that: include, The template agent, carbon source, and nitrogen source are dissolved in a solvent to obtain a homogeneous mixture, wherein the mass ratio of the template agent, carbon source, and nitrogen source is (1~5):(2~8):(0.5~3). The homogeneous mixture is applied to the substrate surface and pre-cured to form a gel film; Under an inert atmosphere, the gel membrane is heated to 600~1200℃ and kept at that temperature for 1~5 h to complete carbonization and removal of the template agent. Then, it is cooled to room temperature to obtain a thin film with a three-dimensional interconnected pore structure. The template agent is any one or two of polystyrene microspheres, silica nanoparticles, and metal-organic frameworks. The nitrogen source is melamine, urea, pyrrole, or polyaniline; The carbon source is glucose, phenolic resin, polyacrylonitrile, or chitosan.
2. The preparation method according to claim 1, characterized in that: The solvent is one of ethylene glycol, glycerol, and pyridine.
3. The preparation method according to claim 1 or 2, characterized in that: The template agent has a particle size of 50~500 nm.
4. The preparation method according to claim 3, characterized in that: The mass concentration of the homogeneous mixture is 15% to 20%.
5. The preparation method according to claim 1 or 4, characterized in that: The pre-curing conditions are as follows: first, dry at 50~90℃ for 6~24 h, then heat-treat at 120~200℃ for 1~3 h.
6. The preparation method according to claim 5, characterized in that: The carbonization process is divided into two stages. The first stage involves heating the temperature to 300-500℃ and holding it there for 0.5-2 hours. Second stage: Heat to 600~1200℃ and hold for 0.5~3 hours.
7. The preparation method according to any one of claims 1, 2, 4, and 6, characterized in that: It also includes, Transition metal nanoparticles with a particle size of 5–30 nm and a loading amount of 1–10 wt% were loaded onto the surface of a three-dimensional interconnected pore structure thin film.
8. The high-flux, high-porosity thin film prepared by any one of claims 1 to 7, characterized in that: The film has a nitrogen content of 3-12 at%, a porosity of 85-98%, and a specific surface area ≥1200 m². 2 / g.
9. The application of the high-flux, high-porosity thin film as described in claim 8 in the preparation of supercapacitor electrode materials and OER catalytic materials.
10. The application of the high-throughput, high-porosity thin film as described in claim 8 as a lithium-sulfur battery separator, gas separation membrane, or flexible sensing substrate.